(untitled) (Journal of the College of Education for Women, 2022)
The present theoretical study analyzes the legacy of the Chicago School of Urban Sociology and evaluates it in the light of the growth and development of Chicago City and the establishment of sociology in it. Sociology has become an academic discipline recognized in the United States of America in the late nineteenth century, particularly, after the establishment of the first department of sociology in the University of Chicago in 1892. That was during the period of the rapid industrialization and sustainable growth of the Chicago City. The Chicago School relied on Chicago City in particular, as one of the American cities that grew and expanded rapidly in the first two decades of the twentieth century. At the end of the nineteenth century, the city witnessed the arrival of large numbers of immigrants from Europe and South America. Accordingly, this study aims to examine the heritage of the Chicago School in depth, focusing on its origin, genesis, and development of the Chicago School of Urban Sociology. It also sheds light on its emergence and dominance over the American academic edifice in the first two decades of the twentieth century. The study further aims to investigate the role of the pragmatic thought in the growth and development of this school as a prominent scientific edifice among all American universities. The golden age of this school and the creativity of its pioneers of the scholars continued until the mid-forties. Thus, the study is to explain the causes of its decline after the mid-forties of the last century. Then, it evaluates the reality of this school after the forties until the first two decades of the current millennium. The study concluded that although much of the urban sociology tradition in the Chicago School and its deeply rooted sub-fields was and remains important, constituting a centre to this discipline, this does not mean that the styles and methods of studies conducted under the Chicago School umbrella should be applied to the urban life of today’s cities. This is due to their inadequacy with the reality of urban life in industrial cities today. That is in return is because of the radical transformations at all levels, including economic, social, political and cultural, as well as the modern communication technologies that have changed the face of the world through what is called today globalization.